Cluster typology of business models of start-ups: (example of Slovakia) - Štefan Slávik; Richard Bednár; Ivana Mišúnová Hudáková; Katarína Moravčíková (Administrative Sciences, 2020)
Start-up is an emerging micro-enterprise that has different characteristics to a larger and mature enterprise. Its viability depends mainly on a functioning business model. The purpose of the research study is to identify the basic types of business model regardless of the specific industry, and thus to penetrate deeper into the more general cognition of start-up business making. The research sample contains 106 start-ups, the business models of which are described using fourteen criteria, which are derived from the visualization of canvas. The research sample is divided by cluster analysis (Ward's hierarchical agglomeration method) into nine clusters, hence types of business models. For a better understanding, the clusters were aggregated into four groups with similar business models. Grouping A is characterized by the model with a small range of processes, mostly with higher product differentiation, scarce resources and satisfying the common basic and higher needs. Grouping B is characterized by the model with a large range of processes and higher product differentiation and satisfying the common basic and higher needs or newer practical needs. Start-ups in grouping C have the model with considerable differentiation aimed at satisfying the common needs. Grouping D has the model based on cultivating relationships with customers, cheap satisfying of needs and use of ordinary resources. The models differ the most in the span of operational processes, segmentation and distribution, and differ the least in the relationships between customers, the cost-price ratio and protection against imitation. The practical use of the identified clusters lies in the fact that they are a reflection of the real behaviour of start-ups, they determine the real parameters of business models, and therefore they provide the founders of start-ups with verified patterns, the outlines of which are probably not definitive.
Keywords: 350; business model; cluster analyses; start-up; typology of business models